Upper Jurassic caryophyllids from condensed pelagic deposits of the Umbria-Marche Apennine (Central Italy) - Cipriani, Angelo (2020)
Here we report newly collected corals from Kimmeridgian–Tithonian pelagites of Central and Northern Apennines. They grew on intrabasinal structural highs (Pelagic Carbonate Platforms or PCPs). The highs originated from dismembering and drowning of a vast peritidal carbonate platform during the Early Jurassic Western Tethys rifting stage. The drowning was followed by condensed pelagic sedimentation on the top of PCPs. Findings of both zooxanthellate and probably azooxanthellate corals in these facies shed new light on the Jurassic-Early Cretaceous paleogeography, paleoenvironment and paleoecology of PCPs. The occurrence of zooxanthellate corals in PCP-top condensed successions recently allowed to constrain the bathymetry of these depositional systems to the photic zone (40 – 150 m). The studied material is mostly represented by solitary, probably azooxanthellate corals, associated with light dependent organisms. These specimens usually display elliptical to circular calices DQGKDYHFHUDWRLGDWWDFKHGPRUSKRORJLHV ȴQHO\ granulated costosepta with a clear crown of palis. Pending a more detailed study of their microstructure, these features suggest an assignation to the scleractinian extant family Caryophyllidae. The collected azooxanthellate fauna is oligotypic but abundant, as a possible result of very slow sedimentation rates and extreme condensation. Most of the corals do not display in-life position, being detached from the substrate and randomly arranged within the pelagic deposits; others are attached on ammonites pseudoshells or on other corals. The new occurrence improves the Late Jurassic record of caryophyllids, providing additional constraints on their paleoecology and on the paleoenvironmental evolution of this sector of Western Tethys.